Analysis of the Usefulness of Accounting Data for the Portfolio Decision: A Decision-Theory Approach - Ohlson, James (Journal of Accounting Research, 1972)
James Ohlson, Analysis of the Usefulness of Accounting Data for the Portfolio Decision: A Decision-Theory Approach, Journal of Accounting Research, Vol. 10, Empirical Research in Accounting: Selected Studies 1972 (1972), pp. 45-84